GEOLOGI, KARAKTERISTIK DAN GENESA ENDAPAN LATERIT BAUKSIT PT. ANTAM (Persero) Tbk, UNIT GEOMIN, DAERAH KENCO, KABUPATEN LANDAK, PROVINSI KALIMANTAN BARAT - Fachrul Rozi Ramadhan; Yoga Aribowo; Dian Agus Widiarso; Betraz A (Geological Engineering E-Journal, 2014)
Bauxite mining is one of the business units that started to increase mine in Indonesia because it has considerable economic value in the scale of quantity and quality. One of the prospective locations are in areas Kenco, Landak District, West Kalimantan Province. Kenco is an area that addressed the rest of the development of Cretaceous volcanism consisting of the island of Borneo Volcanic Formations Mensibau with unit members Granodiorite, quartz diorite and diorite, and the Formation of the Kingdom Volcanic Andesite-trachite units and Formations of alluvium and swamp sediment quarter. Bedrock types that tend to be acid-intemediet bauxite will produce certain characteristics that are different from the dominant rock properties of acids or bases. Rock intensively weathered have the potential to form a precipitate lateritic bauxite. Conducted a detailed mapping is the next steps of regional mapping to narrow the area of bauxite mineral mining resource prospects.         Geological aspects and lateritic bauxite deposit genesis process on the site is a very interesting research material. Based on field mapping, Gibsite is the bauxite formed with frame type is the result of weatherin sediment residue on the soil catena. The study area consists of rocks that form lateritisation overburden, soil laterite, iron cap /gossan, saprolite and bedrock layers. Lateritic bauxite deposit formation is largely controlled by bedrock type, time, climate (rainfall), morphology, changes the face of groundwater, and vegetation destruction process involving a series of rocks, minerals leaching, transport and deposition of mineral elements of chemical residues.         Lateritic bauxite sludge characteristics according to the analysis of X-Ray Diffraction (XRD) on a layer of overburden to ore (saprolite layer) shows the mineral composition Nacrite, Kaolinite, Gibsite, Goethite, Quartz, Nordstandite, Hematite, and Dickite. The average mineral formed at neutral pH tends to be acidic by 5-7 and temperatures below 150oC. The analysis of X-Ray Fluorescence (XRF) shows the rock has certain characteristics which, if averaged Aluminum trihydrate (Al2O3) as much as ±33%, Iron (II) trihydrate (Fe2O3) of about ±8.5%, Silicate oxide (SiO2) approximately ± 43%, Titanium oxide (TiO2) approximately ≤1% and total silicate (R-SiO2) approximately ≤7%. Saprolite layer showed a thickening layer on the hillside at an angle of 20 - 25o, while the section near the top of the hill or valley will be thinned. The results showed that the value of XRF levels bedrock formation of bauxite have economic value to the content of Al and Fe but less to a total content of Si and Si.